(untitled) - Tinsley, Barbara J. (Cambridge, UK,New York, 2003)
Exploring the ways in which children learn to be healthy, this book examines children's understanding of health, from early childhood through adolescence, and how it affects their behavior and actual physical health. The study scrutinizes the ways in which parents, other children, schools, media, and children's home and neighborhood influence children's health, attitudes and behavior.
Keywords: Health behavior in children,Medicine, Preventive,Y học, dự phòng; Health promotion; Nâng cao sức khỏe